#TITLE_ALTERNATIVE# - HIENDRO (NIM 23298019); Pembimbing: Prof. H.T.M. Soelaiman, M.SEE., dan Dr.Ir. Pekik Argo Daho, AYONG
Research is done to observe and analyze performance of a double three phase synchronous generator with twelve-pulse bridge rectified output. A model for simulation is developed and validated with experimental results obtained from actual machine in laboratory. The results of the simulation model are in very good agreement with the test results. The model is used to analyze the performance of the machine predicted from influence of rectifier bridges connection, neutral connection, phase shift between two set stator windings and interphase transformer (for parallel bridge connection). The results obtained show that rectifier bridge connection (in series or in parallel) affect to the deformation of generator ac output voltage and current, also to the dc voltage ripple. Unity the neutral deforms the performance of the machine and increase the dc output ripple. Displacement angle between two set stator windings for the generator with twelve-pulse bridge rectified output for minimum voltage harmonic distortion occurs at 30 electrical degree. The generator output voltage and current THD can be reduced by eliminating generator damper windings. Parallel operation of two six-pulse bridge rectifiers with interphase transformer can reduce generator output voltage and current THD and make dc output ripple smoother, but in contrary oscillation takes place in larger time constant and decrease the value of rectifier dc output voltage.